Immediate effect of trunk flexion and extension isometric exercise using an external compression device on electromyography of the hip extensor and trunk range of motion of healthy subjects - Tian-zong Huang; Suhn-yeop Kim (BMC, 2022)
Abstract Background Sacroiliac joints (SIJs) transmitted trunk load to lower extremities through the lumbopelvis. External compression devices across the SIJs could provide stability to the SIJs. A previous study established that using a device known as Active Therapeutic Movement version 2 (ATM®2) has been developed to improve pain and joint range of motion (ROM) in patients with LBP. However, no study has examined the physiological change in the muscle through ATM®2-based exercise thus far. This study aimed to determine the immediate effects of ATM®2 exercise on the contraction timing, back extension endurance, muscle fatigue, and trunk ROM of lumbar and lower limb muscles in healthy subjects. Methods Thirty-six healthy subjects (mean age = 23.16 ± 2.3) volunteered to participate in this study. Subjects were instructed to perform ROM test using sit and reach test, back extensor endurance test using Biering-Sorensen test, erector spinae (ES), lumbar multifidus (LM) fatigue and onset time of Gluteus maximus (GM) in prone hip extension using electromyography before and after trunk flexion and extension isometric exercises. Results The ROM in trunk flexion showed a significant increase of 7.9% after exercise compared to that before exercise (p < 0.05). Relative GM contraction onset timing significantly decreased after exercise (p < 0.05). The result of the Sorensen test after exercise showed a trend of increase in duration time. Muscle fatigue in the LM, however, showed a significant increase (p < 0.05), whereas muscle fatigue in the ES was reduced without statistical significance. Conclusions The results base on this study showed that exercise-based on ATM®2 is an effective exercise protocol with an effect on the biomechanics of healthy subjects. Clinical trial registration numbers KCT0006728. Clinical trial registration date: 09/11/2021.